DIDACTIC CHARACTERISTICS OF AN ARTIFICIAL INTELLIGENCE-BASED EDUCATIONAL ENVIRONMENT - Nazarova Gulshod Khodjiyevna (INTEGRATION OF EDUCATION AND SCIENCE: GLOBAL CHALLENGES AND SOLUTIONS, 2026)
The integration of artificial intelligence (AI) into education has become one of the most significant directions in the modernization of contemporary teaching and learning processes. AI-based educational environments provide adaptive, personalized, and interactive learning opportunities that enhance the effectiveness of educational activities and improve learner engagement. This article examines the didactic characteristics of artificial intelligence-based educational environments and analyzes their pedagogical significance in modern education. The research explores the role of intelligent technologies in supporting individualized instruction, automated assessment, continuous feedback, and learner autonomy. Qualitative and theoretical research methods, including comparative analysis, content analysis, and synthesis of scientific literature, were employed to investigate the educational potential of AI technologies. The findings indicate that AI-supported educational systems contribute to the development of critical thinking, creativity, problem-solving abilities, and flexible learning models. The study also highlights the advantages and challenges associated with implementing artificial intelligence in education, including issues related to ethics, digital literacy, data privacy, and teacher adaptation. The research concludes that AI-based educational environments possess significant didactic potential for improving educational quality and transforming traditional pedagogical approaches in the digital era.